The FCC, The Coverage Principle of the Fairness Doctrine and the First Amendment - Chamberlin, Bill F. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
This review of the history of the coverage principle developed by the Federal Communications Commission (FCC) concludes that government regulation of mass media program content can be dangerous and that the coverage principle needs to be abolished. The first section of the report discusses the FCC's interpretation of the 1934 Communications Act from 1949 to 1959, the second section describes the FCC's shift in policy in the early 1960s concerning public issues programing, the third section presents the FCC's reassertion of the coverage principle during the period from 1969 to 1973, the fourth section explains the development of a new policy based on the 1974 Fairness Report, and the last section of the review outlines the Commission's policy as of 1979. An analysis of applications of the doctrine is presented to support the theory that broadcast licensees believe they would take a greater risk in airing controversial programing than if they did not. (AEA)
ERIC Note: Paper presented at the Annual Meeting of the Association for Education in Journalism (62nd, Houston, TX, August 5-8, 1979).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Broadcast Industry; Federal Regulation; Freedom of Speech; Mass Media; Programing (Broadcast); Fairness Doctrine -- Federal Communications Commission; Speeches/Meeting Papers; Historical Materials